Standard operating procedure - Gourevitch, Philip (Penguin Press, 2008)
Collects the stories of the American soldiers who took and appeared in the controversial digital photographs from Abu Ghraib, in a collaborative account of Iraq's occupation that reveals how it is being experienced by both guards and prisoners.